التسويق الداخلي ودوره في تحسين جودة الخدمات المصرفية "دراسة ميدانية عن المصارف الخاصة في اللاذقية" - ديب, كندة; بركات, حيان (Latakia University Journal - Economic and Legal Sciences Series, 2016)
This research aims at studying the internal marketing and its importance since it is considered a modern concept of human resources management. It is also a strategy that can help companies to improve the quality of their provided services.The field study was carried out on private banks in Lattakia. A survey was distributed on the employees of these banks. Another survey was distributed on clients of the studied banks. After that, the given answers were analyzed using the statistical program SPSS.The study came to a conclusion that there is a good implementation of internal marketing procedures included in the research: training, empowering employees, rewards and bonuses, job satisfaction and the organization culture.The studied banks were invited to adopt the internal marketing as one of the main concepts and entrances to human resources administration of banks to obtain success in implementation.يهدف البحث إلى دراسة موضوع التسويق الداخلي ومدى أهميته على اعتبار أنه أحد المفاهيم الحديثة لإدارة الموارد البشرية, وكونه استراتيجية يمكن أن تساعد الشركات على تحسين مستوى جودة الخدمة المقدَّمة.تمّت الدراسة الميدانية على المصارف الخاصة العاملة في اللاذقية حيث وُزّعت استبانة خاصة بالعاملين في هذه المصارف, وكذلك استبانة أخرى على زبائن المصارف قيد الدراسة. ومن ثمّ تمّ تحليل الإجابات الواردة باستخدام البرنامج الإحصائي SPSS.خلُصت الدراسة إلى أنّ هناك تطبيقا جيدا لإجراءات التسويق الداخلي التي تضمّنها البحث وهي: التدريب,و تمكين العاملين,و الحوافز والمكافآت, والرضا الوظيفي,وا لثقافة المنظّمة.ودعت الدراسةُ المصارفَ قيد الدراسة إلى تبنّي التسويق الداخلي بوصفه أحد المفاهيم والمداخل الأساس لإدارة الموارد البشرية, مع ضرورة الحصول على الدعم الكافي من الإدارة العليا للمصارف لضمان النجاح في عملية التطبيق.